PENGARUH SENAM OTAK (BRAIN GYM) TERHADAP TINGKAT KECEMASAN MAHASISWA MENGHADAPI PRAKTIK KLINIK - Sesmiyarti " "; Ganis " Indriati; Bayhakki " " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Anxiety is accumulation of tension, causing anxiety and loss of control resulting in motor tension, autonomic nervous system hyperactivity and increased alertness. Anxiety manifests as headaches, trembling, anxiety, palpitations, shortness of breath, sweating and other symptoms of the digestive system. The purpose of this research was to determine the effect of brain gym on anxiety level of  students whose facing first clinical practice. This research used quantitative approach with quasy experiment with pre and post control group design. The population was 30 of second semester’s student, that taken by simple random sampling technique. Data collected by using HARS questionnaires, and tested by dependent t test and independent t test. This research found that there was difference of brain gym on anxiety of experimental and control group (p value = 0.000). This research suggest to student to do brain gym brain gym to reduce their anxiety before clinical practice. Keywords: Clinical practice, brain gym, the level of anxiety, nursing’s student.